Relationship between Prostate Cancer and Sexual Activity: A Case-Control study - Seif Rabiei, Mohamad Ali; Mousavibahar, Seyed Habibollah; Jafari, Masoud; Amiri, Jalaleddin; sanaei, zahra (Social Determinants of Health, 2017)
Background: Prostate cancer is the fourth most and one of the most prevalent cancer in worldwide and Iran respectively. that has both environmental and genetic risk factors. Recently, the role of sexual activity has been considered as a possible risk factor. We conducted this study to evaluate the role of sexual activity in prostate cancer Methods: This case-control study enrolled 120 patients, 59 with prostate cancer and 61 with other urologic conditions in the Urology Ward of Shahid Beheshti Hospital, in Hamadan, Iran in 2016. We used an individual matching technique to control for confounders (age, weight, etc). A self-structured questionnaire was used to gather required informations such as sexual habits of the participants. Finally, data were analyzed with SPSS 16. Results: The mean sexual activity (per week) for the last 5-10 years was 1.78±1 in the case group and 1.6±0.2 in the control group (P=0.26). Participants exhibited different sexual patterns during different age strata: at age 71-80 years and >80 years the sexual activity in 5-10 years before diagnosis (days per week) in case group was more significant than control group respectively P=0.001 and P=005 also sexual activity (days per week) at age 71-80 years in one year before diagnosis was more significant in case group in comparison with control group (P=0.033). Conclusion: The results indicated different impact of sexual activity in different age in patients with prostate cancer. Additional studies, especially meta-analysis or systematic review, should be conducted to clarify this issue.